Using dates phoenix dactylifera l. to improve energy metabolism in fatigue-induced sprague dawley rats - Kadum, Hana; Hamid, Azizah; Abas, Faridah; Ramli, Nurul Shazini; Jaafar, Ahmad Haniff; Pak Dek, Mohd Sabri; Muhialdin, Belal J.; Halim, Hani Hafeeza; Mohammed, Abdul Karim Sabo; Ibrahim, Salam A. (Elsevier, 2021)
Fatigue increases oxidative stress which damages body cells and increases the risk for the development of various chronic diseases. In this study, the anti-fatigue activity of Piyarom date extract was evaluated in fatigue-induced rats using a forced swimming test (FST). Results showed that rats treated with 500 mg/kg BW date extract exhibited enhanced energy production with a highest endurance capacity (632.9±28.7 min). The date-treated rats also had lower blood lactate, indicating efficient energy utilization with lower fatigue as compared to normal and fatigued rats. Moreover, the serum lactate dehydrogenase levels in 250 and 500 mg/kg BW date extracts and caffeine groups were significantly lower compared to the fatigued rats. Creatine kinase activity was the lowest in the group fed with 500 mg/kg BW date extract. The treated rats showed an amelioration of lipid profiles, while the histological study revealed improvement in various organs. Rats treated with 500 mg/kg BW date extract demonstrated an enhancement in energy production and improved energy metabolism which could be due to the presence of bioactive compounds in the dates. Piyarom date extract demonstrated anti-fatigue property and could be used as a functional ingredient in the development of beverages or snacks that address fatigue associated maladies.